Chlorocyanoborates: Synthesis, Spectroscopic and Structural Characterization, and Properties of Ionic Liquids. Issue 21 (17th August 2018) - Bischoff, Lisa A.; Sprenger, Jan A. P.; Hennig, Philipp T.; Ignat'ev, Nikolai V.; Finze, Maik
Abstract : A set of first mixed chlorocyanoborates was synthesized and fully characterized by elemental analysis, NMR and vibrational spectroscopy. Two different synthetic approaches were developed: Exchange of chlorine against CN in case of [BCl3 (CN)] – and reaction of [BH x (CN)4– x ] – with Cl2 or t BuOCl for the generation of [BCl x (CN)4– x ] – ( x = 1, 2). The single‐crystal structures of [Ph4 P][BCl2 (CN)2 ] and [Ph4 P][BCl3 (CN)] were derived from X‐ray diffraction experiments. [EMIm][BCl x (CN)4– x ] ( x = 1–3) and [BMPL][BCl x (CN)4– x ] ( x = 1, 2) were found to be low‐viscosity room temperature ionic liquids. [EMIm][BCl(CN)3 ] (18.6 mPa· s) and [EMIm][BCl2 (CN)2 ] (19.6 mPa· s) are even less viscous than the well‐known [EMIm][B(CN)4 ] (EMIm‐TCB, 22.6 mPa· s). Mono‐ and dichlorocyanoborates were studied by CV and found to provide large electrochemical windows. Especially [EMIm][BCl(CN)3 ] reveals a high specific conductivity (14.1 mS cm –1 ). Abstract :